Hubungan Sumber Informasi terhadap Pengetahuan Remaja Tentang Hidup Bersih Sehat di Desa Nunkurus Kecamatan Kupang Timur - Ermi Lilianda Alang; Ninick Corea Fernandez; Diah Ayu Dwi Satiti; Ni Putu I.D.P. Murti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Clean and Healthy Living Behavior in Indonesia includes household.. In Indonesia, the level of knowledge and handwashing behavior of is still relatively low, an indication can be seen from the high prevalence of diarrhea. Research Objective: to determine the Relationship of Information Sources to Knowledge and Behavior of Adolescents About Clean Living in Nunkurus Village, East Kupang District. Research Method: This type of research uses Quasi Experiment One Group PreTest-PostTest Non Control Group, namely research with one subject who is given treatment or intervention before and after treatment. The population in this study is the community in this case adolescents in Nunkurus Village, East Kupang District, totaling 45 people. Sampling uses a total sampling technique. There are 3 research instruments used in this study including: respondent characteristic questionnaire, PHBS knowledge and health promotion educational video about PHBS. Data analysis using univariate in percentage and bivariate using Willcoxon Test. Results: the results of the study revealed the level of knowledge of the community before health promotion regarding PHBS, of the 45 respondents studied as many as 2 respondents (4.4%) had insufficient knowledge, 14 respondents (31.1%) had sufficient knowledge, and 29 respondents (64.4%) had good knowledge. From the results of the study, it was known that the level of knowledge of the community after health promotion regarding PHBS, of the 45 respondents studied as many as 17 respondents (37.8%) had good knowledge, 20 respondents (44.4%) had sufficient knowledge, and 8 respondents (17.8%) had insufficient knowledge. This is demonstrated by the results of the Wilcoxon ρ test (Asymp. Sig. 2-tailed) = 0.000 <0.05, indicating a relationship.